Optimizing Reconstruction in Craniosynostosis: Review of Nonsyndromic Patients Treated With a Novel Technique. Issue 5 (July 2020) - Rudy, Hayeem L.; Herman, Sean; Stern, Carrie S.; Staffenberg, David A.; Dowling, Kamilah; Goodrich, James T.; Tepper, Oren M.
Abstract : Purpose: Open cranial vault remodeling (CVR) with autologous split calvarial bone grafts redistributes and recontours an abnormal calvarium to create an expanded cranial vault in patients with craniosynostosis. We report a 12-year retrospective review of 162 nonsyndromic patients who underwent operative repair using our previously-described technique which portends excellent surgical outcomes and can be applied to patients of any age group and with any variety of suture fusion. Methods: Data was gathered on patients who underwent CVR from 2005 to 2016. Surgical records for each patient were analyzed and included operative time, estimated blood loss, and intraoperative transfusion volumes. Intraoperative and postoperative complications, the need for revision surgery, postoperative length of stay, and follow-up records were also reviewed. Syndromic patients were excluded, as well as patients with incomplete data sets. Patients who underwent either anterior or posterior vault remodeling were compared. Results: A total of 162 patients were included in this case series. Patients undergoing anterior CVR were significantly older than those undergoing posterior CVR (13.3 versus 11.0 months, P  < 0.015) and also had significantly greater intraoperative red blood transfusion volumes (20.3 versus 15.3cc/kg, P  < 0.0207) and longer operative time than posterior CVR patients (274.9 versus 216.7 minutes, P  < 0.0001). No patients required reoperation for resorption or recurrence or persistent contour irregularities. There were no visual or neurological complications. Calvarial bone was successfully split in 100% of cases. Conclusions: This surgical approach to CVR results in good surgical outcomes with a low recurrence rate, while also maximizing operative efficiency, and minimizing total blood loss and transfusion volume. This technique can be applied to any affected suture in a patient with craniosynostosis and in patients of any age group. Abstract : Supplemental Digital Content is available in the text